6-Amino-7-Azaindoles synthesis from 2, 6-diamino pyridine and diols. (9th November 2021) - Bou-Puerto, Amelia; Bellezza, Delia; Martinez-Morro, Carlota; Gonzalez-Sanchis, Nerea; Ballesteros, Rafael; Cuñat, Ana C.; Ballesteros-Garrido, Rafael
Graphical abstract: Abstract: 6-Amino-7-azaindole has been prepared by combination of diaminopyridine and diols by means of an acceptorless dehydrogenative condensation. In addition, amino pyridines may also yield towards pyrrolo[3, 2- b ]pyrrole systems. All of these transformation have been performed with accessible heterogeneous catalysts: Pd/C and ZnO.